Detection and molecular characterisation of noroviruses in hospitalised children in Malawi, 1997–2007. Issue 7 (22nd May 2013) - Trainor, Eamonn; Lopman, Ben; Iturriza‐Gomara, Miren; Dove, Winifred; Ngwira, Bagrey; Nakagomi, Osamu; Nakagomi, Toyoko; Parashar, Umesh; Cunliffe, Nigel
Abstract Despite the increasing recognition of noroviruses as major pathogens associated with community‐acquired diarrhoea in children, there are few studies from Africa. Long‐term surveillance studies of rotavirus gastroenteritis in Malawian children have provided an opportunity to undertake a study of the importance and epidemiological features of norovirus infection in this population. Faecal specimens were collected from children <5 years of age admitted to hospital with acute diarrhoea, as well as from a comparison group of diarrhoea‐free children, in Blantyre, Malawi between 1997 and 2007. Norovirus was detected using real‐time PCR and strains genotyped by nucleotide sequence analysis. Norovirus was detected in 220/1, 941 (11.3%) faecal specimens, comprising genogroup GI (1.8%), GII (9.4%) and mixed GI/GII (0.1%). The median age of children with norovirus was 6 months (range, 0–48 months). Norovirus was detected throughout the year, with peaks at the end of the rainy season (March) and towards the end of the dry season (August–November). Norovirus GII.4 was the most commonly detected genotype accounting for 70% of strains characterised, followed by GII.2 (6%), GII.6 (4%) and GII.12 (4%). Sub typing of GII.4 noroviruses demonstrated local circulation of strains prior to their subsequent detection in association with global epidemics of gastroenteritis. The prevalence of norovirus in children without diarrhoea was similar to the level in cases. This largest study to date of norovirus infection in African children indicates the potential role of paediatric surveillance in predicting the emergence of norovirus strains with global epidemic potential. J. Med. Virol. 85:1299–1306, 2013. © 2013 Wiley Periodicals, Inc.